ELECTRONIC BUSINESS CONCEPT IN MARKETING OF VILLAGE LEADING PRODUCTS - Yudo Devianto; Saruni Dwiasnati (STMIK Pringsewu Lampung, 2020)
In preparing to welcome the era of technology 4.0, especially preparing rural communities to be ready to accept the arrival of the era of technology 4.0, how can rural communities utilize the technology for their interests. Especially how rural communities can promote superior products produced by the community in general as well as rural communities in particular by using these technologies. In this research, it will be discussed how the application of E-Business can help marketing superior village products, and based on the mandate of law number 6 of 2014